Access to Methotrexate Monitoring in Latin America: A Multicountry Survey of Supportive Care Capacity - Villanueva, G (2024)
High-dose methotrexate (HDMTX) is used to treat a broad spectrum of cancers. Methotrexate (MTX) monitoring and adequate supportive care are critical for safe drug administration; however, MTX level timing is not always possible in low- and middle-income countries. The aim of this study was to evaluate HDMTX supportive care capacity and MTX monitoring practices in Latin America (LATAM) to identify gaps and opportunities for improvement. A multicenter survey was conducted among LATAM pediatric oncologists. Twenty healthcare providers from 20 institutions answered the online questionnaire. HDMTX was used to treat acute lymphoblastic leukemia (ALL; 100%), non-Hodgkin lymphoma (84.2%), diffuse large B-cell lymphoma (47.4%), osteosarcoma (78.9%), and medulloblastoma (31.6%). Delays in starting HDMTX infusion were related to bed shortages (47.4%) and MTX shortages (21.1%). MTX monitoring was performed at an in-hospital laboratory in 52%, at an external/nearby laboratory in 31.6%, and was not available in 10.5%. Median interval between sampling and obtaining MTX levels was ≤ 2 h in 45% and ≥ 6 h in 30%, related to laboratory location. Sites without access to MTX monitoring reduced the MTX dose for patients with high-risk ALL or did not include MTX in the treatment of patients with osteosarcoma. Respondents reported that implementation of point-of-care testing of MTX levels is feasible. In LATAM, highly variable supportive care capacity may affect the safe administration of MTX doses. Improving accessibility of MTX monitoring and the speed of obtaining results should be prioritized to allow delivery of full doses of MTX required by the current protocols.